Excellence Service Strategy through Laboratory System Development in Health Department - Selviyanti, Erna; Roziqin, Mochammad Choirur; Putra, Dony Setiawan Hendyca; Swari, Selvia Juwita; Alfiansyah, Gamasiano; Melinda, Tashya Eka; Tazania, Nur Shabrina Artaf (P3M Politeknik Negeri Jember, 2025)
The Health Department has nineteen laboratories that serve various important purposes, including practicums and learning, supporting clinical research, clinical case simulations, research and system development, professional training, and health services. Despite their significance, these laboratories face challenges in presenting their profiles effectively to the public and stakeholders. This research aims to develop an Information System designed specifically for these laboratories to improve visibility and access to information regarding their services, technology, achievements, and advantages. The research follows a prototyping method to develop the system, which is chosen due to its flexibility, the complexity of the laboratories' needs, and the iterative nature of system development. The research was conducted over a period of six months, and the main steps involved included: early prototype development, rapid design and system testing. The web-based Laboratory Information System has been successfully developed and deployed, effectively addressing the challenges of information presentation, and supporting the growth and development of the laboratories.